Geological occurrence, mineralogical characterization, and risk assessment of potentially carcinogenic erionite in Italy. (17th February 2017) - Giordani, Matteo; Mattioli, Michele; Ballirano, Paolo; Pacella, Alessandro; Cenni, Marco; Boscardin, Matteo; Valentini, Laura
ABSTRACT: Erionite is a zeolite representing a well-known health hazard. In fact, exposure of humans to its fibers has been unequivocally associated with occurrence of malignant mesothelioma. For this reason, a multi-methodological approach, based upon field investigation, morphological characterization, scanning electron microscopy (SEM)/energy-dispersive spectroscopy (EDS) chemical analysis, and structure refinement through X-ray powder diffraction (XRPD), was applied to different samples of potentially carcinogenic erionite from Northern Italy. The studied crystals have a chemical composition ranging from erionite-Ca to erionite-Na and display variable morphologies, varying from prismatic, through acicular and fibrous, to extremely fibrous asbestiform habits. The fibrous samples were characterized by an unusual preferred partition of aluminum (Al) at tetrahedral site T1 instead of tetrahedral site T2. Further, a mismatch between the a-parameter of erionite-Ca and levyne-Ca that are intergrown in the asbestiform sample was detected. This misfit was coupled to a relevant micro-strain to maintain structure coherency at the boundary. Erionite occurs in 65% of the investigated sites, with an estimated quantity of 10 to 40 vol% of the associated minerals. The presence of this mineral is of concern for risk to human health, especially if one considers the vast number of quarries and mining-related activities that are operating in the zeolite host rocks. The discovery of fibrous and asbestiform erionite in Northern Italy suggests the need for a detailed risk assessment in all Italian areas showing the same potential hazard, with specific studies such as a quantification of the potentially respirable airborne fibers and targeted epidemiological surveillance.